Conversion of sodium salicylate to salicylic acid by bipolar electrodialysis : the limiting current density - 315015 Law, Jeng Yih; Masniza Sairi; Mohamad Roji Sarmidi; Regional Symposium on Membrane Science and Technology (2004 : Johor Bahru) (Skudai : Universiti Teknologi Malaysia, 2004)
50